Pengembangan Media Game Edukasi pada Mata Pelajaran IPAS Materi Rangka, Sendi, dan Otot Kelas VI SD Negeri 40 Pontianak Utara - Futrisari, Maissy Ditha; Kresnadi, Hery; Salimi, Asmayani (Pendidikan Islam Anak Usia Dini STIT Palapa Nusantara, 2024)
This research aims to produce a product in the form of an educational game media for the IPAS subject with material on the Skeleton, Joints, and Muscles in the sixth grade of SDN 40 Pontianak Utara that can be considered suitable for use. The research and development (R&D) method is employed, adapting the Thiagarajan 4D development model, which includes the stages of Define, Design, Development, and Dissemination. The data sources for this research come from the validation results of two expert validators, practicality questionnaires for teachers, and feedback from students. Data collection involves validators' validation questionnaires and practicality questionnaires. The results of the research indicate that during the development process of educational game media, these four stages have been successfully implemented. The validity level of educational game media in terms of media reaches an average of 4.45, categorized as highly valid, while the material aspect obtains an average of 4.6, also categorized as highly valid. The practicality of using educational game media in the IPAS subject with material on the Skeleton, Joints, and Muscles for the sixth grade by teachers achieves a score of 4.47, categorized as very practical, while by students, it reaches a score of 4.1, also categorized as very practical. Based on the obtained results, it can be concluded that the educational game media developed for the IPAS subject with material on the Skeleton, Joints, and Muscles for the sixth grade can be considered suitable for use in the teaching and learning process.